Effect of High Intensity Interval Training (HIIT) on VO2max Capacity of Bhayangkara FC U19 Players - Suliarno, Jefri Wibowo; Pamungkas, Hari; Kurniawan, Rubbi; Nidomuddin, Muhammad; Pradipta, Anangga Widya (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The study was conducted to prove the effect of giving interval training with high intensity (High Intensity Interval Training or HIIT) on the VO2max capacity of soccer players. Materials and methods. Quasi experiment with one group pretest posttest design on Bhayangkara FC football players aged under 19 as many as 25 players. VO2max measurements were taken before and after being given HIIT treatment using the yo-yo intermittent recovery test level 2. Analysis using paired sample t test with the help of the SPSS version 26 application. Results. Paired Sample t-Test results show a significance value of 0.00. This value is much smaller than alpha (0.05), which means that there is a significant difference between VO2max before and after training. Conclusion. Research shows that high-intensity interval training (HIIT) can significantly increase VO2max of Bhayangkara FC U19 football players.